P81-T Homeostatic and metaplastic mechanisms of quadri-pulse theta burst stimulation using an inhibitory priming protocol. Issue 7 (July 2019) - Asenbauer, Elisabeth; Gleich, Bernhard; Gattinger, Norbert; Siebner, Hartwig R.; Mall, Volker; Jung, Nikolai H.
Abstract : Background: Homeostatic plasticity is considered to stabilize neural activity within a physiologically reasonable and dynamic range. Quadri-pulse-thetaburst stimulation (qTBS) is a patterned transcranial magnetic stimulation (TMS) protocol that induced lasting increase/decrease in neuronal excitability of human primary motor cortex (M1) probably corresponding to the model of LTP- and LTD-like plasticity. Methods: We investigated priming mechanisms of inhibitory qTBS on subsequent facilitating qTBS (experiment 1) and on subsequent inhibitory qTBS (experiment 2). Inhibitory qTBS consisted of 360 bursts given continuously to M1, with bursts of four biphasic TMS pulses, separated by inter-stimulus intervals (ISI) of 50 ms (20 Hz) and inter-burst intervals of 200 ms (5 Hz) (qTBS50/200). Facilitatory qTBS consisted of the same burst pattern but with ISI of 5 ms (200 Hz) (qTBS5/200). Resting motor threshold (RMT) and motor evoked potential (MEP) amplitudes were measured before priming (pre) and for 30 min (post1-post3) after priming. Following post 3, the second stimulation was applied and the RMT and MEP were measured for 60 min (post 4 – post7). Results: In experiment 1 (qTBS50/200 – qTBS5/200), priming led to a decrease of MEP amplitudes (post 1–3), while MEP amplitudes increased following qTBS5/200 (post 4–7). In experiment 2 (qTBS50/200 – qTBS50/200), MEP amplitudes decreased following the priming protocol and returned to baseline after the qTBS50/200 protocol. Discussion/conclusion: Our results point towards homeostatic mechanisms of facilitatory qTBS5/200 following priming with qTBS50/200. In contrast, subsequent qTBS50/200 led to a de-depression like effect of MEP amplitudes suggesting metaplastic effects of two inhibitory qTBS protocols applied over M1.